Learning on the Move Toward Just, Sustainable, and Culturally Thriving Futures - Bang, Megan (Cognition and instruction, 2020)
This issue is particularly timely, in its plea to the field to understand that human learning and development have always been on the move-always migrating-even if and when we construct sedentarist bias and territorial boundaries of the nation-state as normative or when we remember or remake as "ambulatory we's" as we engage in "ongoing re-collection and re-membering of dynamic social and spatial relationships". As each paper in the issue makes poignantly clear with important conceptual and methodological contributions, place is always in the making through our movements and relations, through our ways of coming to know and be together, and through our creative and accountable analysis, data, and narrative. Non-movements are social constructions-humans, like all life, are mobile. Non-movement is an historically accumulating bias that serves the long trajectory of powered struggles in western knowledge systems and societies ontological assertions of human exceptionalism and supremacy. Mobilities, migrations, and places-how we see them, how we make them, how we dream them and how we story them-are consequential. Each paper in this issue contributes unique insights into how learning and development are always on the move-even despite the sedentarist bias that has dominated learning and the construction of human knowing and activity since enlightenment-and this issue helps to create new pathways of scholarship.